Analysis of French generic medicines retail market: why the use of generic medicines is limited. (December 2014) - Dylst, Pieter; Vulto, Arnold; Simoens, Steven
Abstract : The market share of generic medicines in France is low compared to other European countries. This perspective paper provides an overview of the generic medicines retail market in France and how the current policy environment may affect the long-term sustainability. Looking at the French generic medicines retail market and the surrounding regulatory framework, all conditions seem to be in place to create a healthy generic medicines market: the country has well-respected regulatory authorities, generic medicines enter the market in a timely manner and prices of generic medicines are competitive compared with other European countries. Despite the success of the demand-side policies targeted at pharmacists and patients, those targeted at physicians were less successful due to a lack of enforcement and a lack of trust in generic medicines by French physicians. Recommendations to increase the use of generic medicines in France round off this perspective paper.